Неомифологема Пушкинианы «Царскосельский отрок»: От Вяземского до Ахматовой - Шарафадина, К. И.
В статье подробно рассмотрены основные знаковые комплексы «лицейско-царскосельской» Пушкинианы: «сады Лицея», иконография адресата, номинация «отрок». Автор впервые устанавливает её прецедентный источник – стихотворение П.А. Вяземского «Поэтической дружины смелый вождь и исполин!». Ахматовская характеристика «смуглый отрок» интерпретирована в ритуально-обрядовом контексте поэтической инициации как генетическом. The article deals with the main sign complexes of the Lyceum-Tsarskoye Selo poetry by Pushkin: "Lyceum Gardens", the portrait of a lyceum student, and the "boy" nomination. The author establishes its precedent text – a poem by P. A. Vyazemsky "Poetic team brave leader and giant!". Akhmatova's characteristic "swarthy boy" is interpreted in the ritual context of initiation as genetic. The author comes to a conclusion about the creation by the efforts of the poets of different generations of the neo-mythologeme "Tsarskoye Selo Pushkin", endowed with diverse semantics: from the biographical to the culturological. Key words: Poetic Pushkiniana, P. Viazemsky, A. Akhmatova, neomythologeme, "Tsar's country boy ", initiation
Keywords: Литературоведение